Experimental Evidence on Acupuncture Targeting Ferroptosis for Neurological Function Improvement in Cerebral Stroke: A Systematic Review and Meta‐Analysis - Wenyu Zhang; Xiaoxi Liu; Xuyang Feng; Donglei Lu; Ruiyu Li; Haizhen Guo; Kun Nie; Xuezhu Zhang (Brain and Behavior)
ABSTRACT Background Acupuncture, a traditional Chinese medicinal practice, has been studied for its ability to regulate ferroptosis and improve neurological function. This systematic review aimed to evaluate the evidence about the effects of acupuncture on ferroptosis and the improvement of neurological function in animal models of cerebral stroke. Methods The research was conducted in accordance with the preferred reporting items for systematic reviews and meta‐analyses (PRISMA 2020) guidelines. We conducted a literature search in web of science, Embase, Ebsco, PubMed, Cochrane library, China biomedical literature database (CBM), China national knowledge infrastructure (CNKI), Wanfang database (WF), and VIP database for Chinese technical periodicals, covering pertinent studies up to May 30, 2024. The inclusion criteria covered experimental animal models of cerebral stroke that underwent acupuncture interventions (electroacupuncture [EA], manual acupuncture [MA], or moxibustion [Moxi]). The primary outcomes consisted of neurological function scores (Longa, modified neurological severity score [mNSS], Zausinger, Garcia, Ludmila Belayev scores, and levels of brain‐derived neurotrophic factor [BDNF]). Secondary outcomes encompassed iron metabolism (iron ion content, ferritin heavy chain 1 [FTH1], transferrin receptor 1 [TFR1]), lipid peroxidation (malondialdehyde [MDA], reactive oxygen species [ROS]), antioxidative parameters (glutathione peroxidase 4 [GPX4], glutathione [GSH], superoxide dismutase [SOD]), and ferroptosis markers (long‐chain acyl‐CoA synthetase 4 [ACSL4]). Two authors independently evaluated the methodological quality of the included studies utilizing the collaborative approach to meta‐analysis and review of animal data from experimental studies (CAMARADES) 10‐item checklist. Results The meta‐analysis indicated that acupuncture markedly enhanced neurological function scores (Longa, Longa [mNSS], Zausinger, Garcia, Ludmila Belayev) and elevated levels of BDNF, GSH, GPX4, and SOD in animal models of cerebral stroke. Furthermore, it significantly reduced the levels of cerebral iron, FTH1, TFR1, MDA, ROS, and ACSL4. Conclusions Acupuncture effectively inhibits ferroptosis and enhances neurological function in animal models of cerebral stroke by modulating brain iron metabolism, decreasing lipid peroxidation, and improving brain antioxidant capacity.